Python/NEURON code for simulating biophysically realistic thalamocortical dynamics during sleep - Fink, Christian G; Sanda, Pavel; Bayer, Logan; Abeysinghe, Eroma; Bazhenov, Maxim; Krishnan, Giri P (Software impacts, 2024)
Understanding the function of sleep and its associated neural rhythms is an important goal in neuroscience. While many theoretical models of neural dynamics during sleep exist, few include the effects of neuromodulators on sleep oscillations and describe transitions between sleep and wake states or different sleep stages. Here, we started with a C++-based thalamocortical network model that describes characteristic thalamic and cortical oscillations specific to sleep. This model, which includes a biophysically realistic description of intrinsic and synaptic channels, allows for testing the effects of different neuromodulators, intrinsic cell properties, and synaptic connectivity on neural dynamics during sleep. We present a complete reimplementation of this previously-published sleep model in the standardized NEURON/Python framework, making it more accessible to the wider scientific community.
Keywords: Sleep; NEURON; Computational neuroscience; Neuromodulation